Corporate urbanization and the computerized city: between hierarchization and territorial selectivity in Brazil - Bicalho, Beatriz; Almeida, Amanda Silva (Geografares, 2026)
This article analyzes the contemporary mediations of corporate urbanization in the Brazilian context. It is argued that such articulation contributes to the production of new norms and forms of command over urban space. It further discusses how mechanisms of territorial hierarchization and selectivity orient municipal agendas that are increasingly directed toward corporate interests and the legitimization of competitiveness. Finally, it concludes that the informatization of cities represents the most consequential development of this model, in which neoliberal rationality deepens historically constructed sociospatial inequalities.